Feminist Pandemic Pedagogies: Podcasting and the Study of Religion - Lee-Shae S. Scharnick-Udemans (Journal for the Study of Religion)
In this article I will explore and share my pedagogical practices and ex-periences as a feminist scholar of religion, within the context of a voluntary postgraduate reading group, during the first nine months of the Covid-19 pandemic. The article is structured in two parts. The first part offers a reflection of the teaching approaches that inspired and enabled the production of a podcast about the study of religion from the perspective of black African students and scholars of religion. The second part conceptualizes the pro-duction of a podcast as a feminist pedagogical experiment and reflects on this process alongside feminist pedagogical principles. While the orientation of this article is tentative and reflexive, it advances the argument that because of the commitment to social justice that is inherent to feminist approaches to scholarship and pedagogy, feminist scholars are generally poised to work within the contexts of crisis. Therefore, within the context of the pandemic, feminist approaches to teaching and learning in the study of religion may yield insights that can contribute to the continued development of sustainable pedagogies that honor the fraught nature of these times for both scholars and students.